Contact stiffness ratio of tribological interface using the equivalent thin layer and the micro-slip model. (January 2020) - Sun, Yunyun; Xiao, Huifang; Xu, Jinwu
In this paper, a method for evaluating the contact stiffness ratio of the elastic rough interface is proposed. The rough contact interface subjected to normal load is replaced by an equivalent thin layer with isotropic material. The interfacial stiffness ratio is characterized using the material parameters of the thin layer. The shear modulus and Young's modulus of the thin layer are determined by introducing the stuck length coefficient combined with the micro-contact analysis of the deformed asperity. The derived stiffness ratio is related to the surface topography, interfacial separation, material properties of the contacting bodies, and the stuck length coefficient. The implicit solution of the stuck length coefficient is also obtained. Variations of the stiffness ratio with the interfacial separation and the normal force are analyzed for different surface topographies and stuck length coefficients. Comparisons between the interfacial stiffness ratio of the proposed method and the experimental results as well as the calculated values of existing models are performed.